PEMBERDAYAAN MASYARAKAT DALAM PEMANFAATAN LIMBAH ORGANIK SEBAGAI UPAYA MENUMBUHKAN EKONOMI KREATIF DI DESA SEUNEUBOK PUNTI KABUPATEN ACEH TAMIANG - Fadhilah Fadhilah; Rizki Amalia; Ekariana S. Pandia (Global Science Society, 2020)
In the village of Seuneubok Punti, Kabupaten Aceh Tamiang is known for its sellers of corn. Every day a lot of organic corn husk waste is produced. However, this waste is only considered as garbage or animal feed. Even though a little creativity has added use value and economic value of the organic corn husk waste. The objectives of the community service program are: (1) To develop a culture of caring and sensitivity for the University of Samudra Mathematics education lecturers and students in the utilization of waste in the surrounding environment; (2) Providing sharing to the community in transforming organic waste of corn husk into varied handicrafts; and (3) Improving the community's economy through marketing handicrafts from organic waste of corn husk. The method for carrying out this community service activity uses the direct approach, lectures, and practices. Indicators of success of the program's activities include: (a) Seuneubok Punti villagers, especially roasted corn traders can make handicrafts from the organic waste of corn husk; and (b) Seuneubok Punti Village people can market the products made. Furthermore, it can also be developed sustainably to improve the economy.